Development of hypoxia and acidification during harmful algal blooms: dynamic multi-stressor conditions in NY, USA, estuaries - Mairead Farrell; Ryan B. Wallace; Adrienne Tracy; Andrew Lundstrom; Christopher J. Gobler (Harmful Algae, 2026)

Leveraging Pharmacy Education through a Train-the-Trainer Model to Enhance Breast Cancer Literacy in Rural Communities - Christopher L. Farrell; Melanie R. Ginzburg; Morgan B. Enlow; Missouri M. Jenkins; Alexus N. Hames; Cayla R. Adams; Marlana A. Roberts; Hillary E. Stamps; Natalie A. Paxton; Courtney N. Addison; Austin Y. Shull (Journal of Cancer Education, 2026)
Rural versus urban communities experience disproportionate challenges in breast cancer outcomes, with higher breast cancer mortality and later stage disease presentation, despite similar diagnosis rates. These disparities are driven by structural barriers, including rural hospital closures, transportation difficulties, and limited access to oncology specialists. This study evaluated a train-the-trainer program designed to equip PharmD students located at a pharmacy school in a rural county in South Carolina with breast cancer education training, leveraging the pharmacists’ position as accessible healthcare professionals in rural communities. Training focused on breast cancer risk factors, prevention, screening, genetics, staging, and treatment options. Effectiveness was measured through pre- and post-workshop confidence surveys and knowledge assessments. Results showed significant improvement in student confidence across educational domains, with average scores increasing from 6.30 to 8.59 ( p < 0.0001). Understanding of screening guidelines (mean difference: 4.30; p -value: < .0001) and target therapy options showed the greatest improvement (mean difference: 3.65; p -value: < .0001), while knowledge of BRCA gene inheritance showed the smallest change (mean difference: 0.369; p -value: ns), suggesting some pre-existing awareness but limited understanding of its clinical applications. Overall, this pilot program demonstrates how pharmacy education can address healthcare disparities in rural communities. By preparing pharmacists to deliver accurate breast cancer education and to increase rural patient agency, this model creates a sustainable approach to improving health literacy in medically underserved areas. Future research could further expand this model to include diverse healthcare professionals and incorporate long-term impact assessments in community settings.

Urban greening and water strategies are key to adapt Australian cities to climate change and urban growth - Valentina Marchionni; Christopher Szota; Claire Farrell; Stephen J. Livesley; Kerry A. Nice; Veljko Prodanovic; Sally Thompson; Pui Kwan Cheung; Hamideh Nouri; Mathew Lipson; Brandon Winfrey (Journal of Hydrology, 2026)

Assessment of CYP2D6 gene expression in liver tissue: Variability in CYP2D6 mRNA levels within genotype-predicted metabolizer phenotype groups - Erika L. Meaddough; Sara M. Sarasua; Deborah Kunkel; Luigi Boccuto; Satishkumar R. Ganakammal; Matt Moersen; Christopher L. Farrell (Chemico-Biological Interactions, 2025)

What doesn’t kill you makes you stronger: Using plant traits to inform species selection for naturalistic plantings in hotter and drier climates - Lavinia Hsiao-Hsuan Chu; Christopher Szota; Stefan K. Arndt; Claire Farrell (Landscape and Urban Planning, 2025)

Temperature matters: Acute and latent toxicity of diluted bitumen to developing salmon is potentiated by a modest increase in water temperature - Derin M. Çalık; Feng Lin; Mackenzie Edgar; Anthony P. Farrell; Christopher J. Kennedy; Todd E. Gillis; Sarah L. Alderman (Aquatic Toxicology, 2025)

Does mycorrhizal colonization of biofilter plants improve their water uptake or drought resistance? - Kanglin Tian; Claire Farrell; Anna Lintern; Yussi M. Palacios; Christopher Szota; Brandon Winfrey (Urban Forestry & Urban Greening, 2025)

Larger shrubs can maintain high infiltration and evapotranspiration rates in experimental biofiltration systems impacted by high sediment loads - Christopher Szota; Sivashneel Sanjappa; Tim D. Fletcher; Claire Farrell (Urban Forestry & Urban Greening, 2024)

Evaluating the effectiveness of spontaneous vegetation for stormwater mitigation on green roofs - Dean Schrieke; Christopher Szota; Nicholas S.G. Williams; Claire Farrell (Science of The Total Environment, 2023)

Influence of green roof plant density and redirecting rainfall via runoff zones on rainfall retention and plant drought stress - Lubaina Soni; Christopher Szota; Tim D. Fletcher; Claire Farrell (Science of The Total Environment, 2023)

Assessing Antigen-Adjuvant Complex Stability Against Physical Stresses By wNMR - Marc B. Taraban; Katharine T. Briggs; Yihua Bruce Yu; Michael T. Jones; Lindsey Rosner; Akhilesh Bhambhani; Donna M. Williams; Christopher Farrell; Mikhail Reibarkh; Yongchao Su (Pharmaceutical Research, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

High water users can be drought tolerant: using physiological traits for green roof plant selection - Claire Farrell; Christopher Szota; Nicholas S. G. Williams; Stefan K. Arndt (Plant and Soil, 2013)

Modelling of fluid–solid interactions using an adaptive mesh fluid model coupled with a combined finite–discrete element model - Axelle Viré; Jiansheng Xiang; Frank Milthaler; Patrick Emmet Farrell; Matthew David Piggott; John-Paul Latham; Dimitrios Pavlidis; Christopher Charles Pain (Ocean Dynamics, 2012)

Microsite and litter cover effects on soil conditions and seedling recruitment in a saline agricultural system - Claire Farrell; Christopher Szota; Richard J. Hobbs; Timothy D. Colmer (Plant and Soil, 2011)

Evolutionary Consequences of Dispersal Ability in Cactus-feeding Insects - Christopher Irwin Smith; Brian D. Farrell (Genetica, 2006)

Phylogeography of the longhorn cactus beetle Moneilema appressum LeConte (Coleoptera: Cerambycidae): was the differentiation of the Madrean sky islands driven by Pleistocene climate changes? - CHRISTOPHER IRWIN SMITH; BRIAN D. FARRELL (Molecular Ecology, 2005)
Although it has been suggested that Pleistocene climate changes drove population differentiation and speciation in many groups of organisms, population genetic evidence in support of this scenario has been ambiguous, and it has often been difficult to distinguish putative vicariance from simple isolation by distance. The sky island communities of the American Southwest present an ideal system in which to compare late Pleistocene range fragmentations documented by palaeoenvironmental studies with population genetic data from organisms within these communities. In order to elucidate the impact of Pleistocene climate fluctuations on these environments, biogeographic patterns in the flightless longhorn cactus beetle, Moneilema appressum were examined using mitochondrial DNA sequence data. Gene tree relationships between haplotypes were inferred using parsimony, maximum‐likelihood, and Bayesian analysis. Nested clade analysis, Mantel tests, and coalescent modelling were employed to examine alternative biogeographic scenarios, and to test the hypothesis that Pleistocene climate changes drove population differentiation in this species. The program mdiv was used to estimate migration and divergence times between populations, and to measure the statistical support for isolation over ongoing migration. These analyses showed significant geographic structure in genetic relationships, and implicated topography as a key determinant of isolation. However, although the coalescent analyses suggested that a history of past habitat fragmentation underlies the observed geographic patterns, the nested clade analysis indicated that the pattern was consistent with isolation by distance. Estimated divergence times indicated that range fragmentation in M. appressum is considerably older than the end of the most recent glacial, but coincided with earlier interglacial warming events and with documented range expansions in other, desert‐dwelling species of Moneilema .

Range expansions in the flightless longhorn cactus beetles, Moneilema gigas and Moneilema armatum , in response to Pleistocene climate changes - CHRISTOPHER IRWIN SMITH; BRIAN D. FARRELL (Molecular Ecology, 2005)
Pollen cores and plant and animal fossils suggest that global climate changes at the end of the last glacial period caused range expansions in organisms indigenous to the North American desert regions, but this suggestion has rarely been investigated from a population genetic perspective. In order to investigate the impact of Pleistocene climate changes and glacial/interglacial cycling on the distribution and population structure of animals in North American desert communities, biogeographical patterns in the flightless, warm‐desert cactus beetles, Moneilema gigas and Moneilema armatum , were examined using mitochondrial DNA (mtDNA) sequence data from the cytochrome oxidase I (COI) gene. Gene tree relationships between haplotypes were inferred using parsimony, maximum‐likelihood, and Bayesian analysis. Nested clade analysis and coalescent modelling using the programs mdiv and fluctuate were used to identify demographically independent populations, and to test the hypothesis that Pleistocene climate changes caused recent range expansions in these species. A sign test was used to evaluate the probability of observing concerted population growth across multiple, independent populations. The phylogeographical and nested clade analyses reveal a history of northward expansion in both of these species, as well as a history of past range fragmentation, followed by expansion from refugia. The coalescent analyses provide highly significant evidence for independent range expansions from multiple refugia, but also identify biogeographical patterns that predate the most recent glacial period. The results indicate that widespread desert environments are more ancient than has been suggested in the past.